Cis- and Trans-Palmitoleic Acid Isomers Regulate Cholesterol Metabolism in Different Ways - Huang, Wen-wen; Hong, Bi-hong; Bai, Kai-kai; Tan, Ran; Yang, Ting; Sun, Ji-peng; Yi, Rui-zao; Wu, Hao (Frontiers in Pharmacology, 2020)
Hypercholesterolemia is a preventable risk factor for atherosclerosis and cardiovascular disease. However, the mechanisms whereby cis-palmitoleic acid (cPOA) and trans-palmitoleic acid (tPOA) promote cholesterol homeostasis and ameliorate hypercholesterolemia remain elusive. To investigate the effects of cPOA and tPOA on cholesterol metabolism and its mechanisms, we induced hypercholesterolemia in mice using a high-fat diet and then intragastrically administered cPOA or tPOA once daily for 4 weeks. tPOA administration reduced serum cholesterol, low-density lipoprotein, high-density lipoprotein, and hepatic free cholesterol and total bile acids (TBAs). Conversely, cPOA had no effect on these parameters except for TBAs. Histological examination of the liver, however, revealed that cPOA ameliorated hepatic steatosis more effectively than tPOA. tPOA significantly reduced the expression of 3-hydroxy-3-methyl glutaryl coenzyme reductase (HMGCR), LXRα, and intestinal Niemann-Pick C1-Like 1 (NPC1L1) and increased cholesterol 7-alpha hydroxylase (CYP7A1) in the liver, whereas cPOA reduced the expression of HMGCR and CYP7A1 in the liver and had no effect on intestinal NPC1L1. In summary, our results suggest that cPOA and tPOA reduce cholesterol synthesis by decreasing HMGCR levels. Furthermore, tPOA, but not cPOA, inhibited intestinal cholesterol absorption by downregulating NPC1L1. Both high-dose tPOA and cPOA may promote the conversion of cholesterol into bile acids by upregulating CYP7A1. tPOA and cPOA prevent hypercholesterolemia via distinct mechanisms.